2022
DOI: 10.3389/fmed.2022.986968
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of stress in patients with Lupus

Abstract: BackgroundStress is common in patients with Systemic Lupus Erythematosus (SLE), and is associated with depression, fatigue, and disease flares. Stress may be modifiable and identifying those at high risk allows clinicians and allied health care professionals to develop a multidisciplinary management plan to direct appropriate resources. This study is aimed at identifying predictors of high stress over time among patients with SLE.MethodsLongitudinal data from two interviews of the Lupus Outcomes Study 2 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
3
1
1
Order By: Relevance
“…There is inconsistent information regarding the prevalence of these manifestations among males. The discrepancy between our result and previously reported negative associations could be attributed to the variation in the screening tools used [ 24 ]. Despite SLE’s impact on neuropsychiatric health, there is still a lack of data regarding the prevalence of depression in males compared to females, mainly due to a lower prevalence of the disease in male patients [ 42 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There is inconsistent information regarding the prevalence of these manifestations among males. The discrepancy between our result and previously reported negative associations could be attributed to the variation in the screening tools used [ 24 ]. Despite SLE’s impact on neuropsychiatric health, there is still a lack of data regarding the prevalence of depression in males compared to females, mainly due to a lower prevalence of the disease in male patients [ 42 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Being unemployed is a predictor for anxiety and depression among the general population [23], and the correlation between unemployment and anxiety/depression was confirmed in the current study, especially with the high reported percentage of unemployment among participants. Along the same lines, recent studies found a higher anxiety and depression rate in patients with lower incomes [22,24]. Unemployment has shown a direct relationship with abnormal immune function through increased production of cytokines [25] and other biomarkers [26].…”
Section: Discussionmentioning
confidence: 80%
“…H-QoL appears to be linked with unfavorable outcomes in SLE [43] alongside depressive symptoms and stress [14]. Therefore, the prevention, early identification, and treatment of mood disorders are crucial for individuals with SLE and should consider their multifactorial pathogenesis involving both direct (e.g., antineuronal antibodies, pain) and indirect (e.g., glucocorticoids, relationship issues, comorbidities) factors [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the effect of the stress of living with a chronic illness must be considered. It is only recently that emerging evidence has begun to suggest that the presence of depressive syndromes may serve as a determinant for a significant impairment of H-QoL among SLE patients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Lupus merupakan penyakit autoimun kronis yang memerlukan perawatan jangka panjang (E. Handono et al, 2017;Leung et al, 2021). Pasien lupus dan keluarga dihadapkan dengan berbagai stresor dan tantangan meliputi kondisi penyakit yang naik turun, kondisi pasien yang sering mengalami mood swing, keharusan kontrol ke layanan kesehatan setiap bulan, minum obat setiap hari, menghadapi efek samping obat yang bermacam-macam dan tidak menyenangkan, biaya obat dan perawatan yang tidak murah, menghadapi respons sekitar yang beraneka ragam, hingga komplikasi IJCSL P-ISSN: 2579-7166 E-ISSN: 2549-6417 penyakit pada panca indera, jantung, paru, kandungan, dan saraf (Berger & Font, 2015;Cojocaru et al, 2022;Harnadia et al, 2021;Jolly & Katz, 2022;Sari Dewi et al, 2016). Diperlukan dukungan yang kuat baik bagi pasien maupun keluarga agar mampu menghadapi sakitnya dengan tenang (E. S. Jannah et al, 2022;Lombard, 2017).…”
Section: Pendahuluanunclassified